SOSIALISASI PENTINGNYA VAKSIN COVID-19 DAN PEMBAGIAN MASKER DALAM RANGKA ADAPTASI DI ERA NEW NORMAL - Herman Lawelai; Asrin; Alnamira; Kasmaludin; Haris (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Coronavirus Disease 2019 (COVID-19) is a deadly virus whose transmission is getting used to the COVID-19 vaccine and wearing a mask. The COVID-19 vaccine and wearing masks not only protect people who are infected with COVID-19 but also the community to prevent the transmission of COVID-19 in general. Vaccines, apart from being used as a barrier to prevent the transmission of COVID-19, have also been shown to reduce the number of positive cases of COVID-19. The implementation of this service took place in Kambula-Bulana Village, Pasarwajo District, Buton Regency. Dissemination of the need for attention to road users who lack knowledge about vaccination, especially in the prevention of COVID-19. Our partners are divided into two parts, Lack of knowledge about the covid-19 vaccine and Develop a caring attitude by using masks when doing activities outside the home and in crowds to help limit the spread of COVID-19. This effort began by going directly to the public and road users to provide information about the causes, symptoms, and prevention of COVID-19, as well as providing education about COVID-19 vaccination. The next action was the distribution of masks, followed by a discussion about the need to comply with health procedures. In addition to washing hands and maintaining a safe distance, the use of appropriate and appropriate masks is another form of prevention.